DEVELOPMENT OF INNOVATIVE IDEAS IN IMPLEMENTATION OF LOVE CURRICULUM - M. Alang Khairun Nizar (International Journal of Educational Review, Law And Social Sciences (IJERLAS), 2025)
The Ministry of Religion of the Republic of Indonesia is currently initiating the Love Curriculum, an educational initiative that aims to instill the values ​​of love for God, fellow human beings, the environment, and the nation from an early age.The method of writing the results of the review article research begins with a gap analysis followed by the PRISMA (Preferred Reporting Items for Systematic Reviews and Meta-analyses) method. The PRISMA method consists of 5 stages carried out: 1) defining eligibility criteria, 2) determining sources of information, 3) selecting data, 4) collecting data, and 5) taking data. This curriculum emphasizes four main aspects. "First, building love for God (Hablum Minallah), where children are accustomed to strengthening their relationship with Allah from an early age. "Second, building love for fellow human beings, regardless of religion. Children must be accustomed to diversity, building a strong Hablum Minannas. "Third, forming concern for the environment (Hablum Bi'ah). fourth, love for the nation (Hubbul Wathan). With the implementation of the Love Curriculum, it is hoped that Indonesia can produce a generation that is more tolerant, inclusive, and full of compassion—creating a harmonious society in diversity.